Optical solitons to time-fractional Sasa-Satsuma higher-order non-linear Schrodinger equation via three analytical techniques - Raheel, M.; Zafar, Asim; İnç, Mustafa; Tala-Tebue, E. (Springer, 2023)
This current research is about the exact solitons of time-fractional Sasa-Satsuma higher order non-linear Schrodinger equation with novel definition of derivative that are achieved with the use of three analytical methods i.e extended Jacobi's elliptic expansion function method (EJEEFM), exp(a) function method and Kudryashov method. The obtained optical solitons are verified with the use of Mathematica software. Finally, different graphs are also drawn of the gained solutions. The main purpose of our work is to explain the effect of beta-time fractional derivative on the solutions of Sasa-Satsuma equation that are gained with the use of EJEEF, exp(a )function, Kudryashov methods. These exact solitons show that these three techniques are efficient, simple and reliable than other techniques.
Keywords: Sasa-Satsuma equation; Beta-time fractional derivative; EJEEFM; exp(a) function method; Kudryashov method; soliton